Management Techniques and Lecturers Output in Obafemi Awolowo University, Ile-Ife, Nigeria - Ajadi, Olugbenga Timothy (Indonesian Journal of Education and Social Sciences, 2025)
Publication and teaching cannot be underrated when measuring lecturers output in the university.  This is because, lecturers output is central to research and training, career progression and university global ranking.  The study generally identified the various management strategies and their implications for lecturer’s publication and teaching output.  Specifically, it investigated the most prominent management strategies used, the level of lecturers’ publication and teaching output and the influence of management strategy on lecturers’ output in Obafemi Awolowo University, . The population of the study comprised 1,225 academic staff of the university with a sample size of 250 using multistage sampling procedure. Questionnaire titled Management Techniques and Lecturers Output Questionnaire (MTLOQ) was used to elicit information from respondents.  The study found participative management strategy as the most prominent strategy in Obafemi Awolowo University, followed by delegative and authoritative strategies  In addition, the level of lecturer’s publication was low with 175 low google scholar appearance, 196 low high citation counts, 155 do not publish frequently, 192 with low number of publications and 172 do not published in indexed journals and teaching output was high with 203 respondents having high good students performance, 178 having high frequent student feedback, 207 recorded high graduation rates and 191 recorded high student class participation.  It was recommended that the university should take over the payment of lecturer’s publication in high impact journals to increase the university and lecturer’s visibility.  The university can also attach monetary incentive to lecturers with good number of publications in indexed journals.